2021
DOI: 10.1002/cam4.4078
|View full text |Cite
|
Sign up to set email alerts
|

HOXD13 promotes the malignant progression of colon cancer by upregulating PTPRN2

Abstract: Purpose The homeobox (HOX) family plays an important role in multi‐biological processes, such as morphogenesis and tumors. However, the function of HOXD13 in colon cancer remains unclear. Materials and Methods The Cancer Genome Atlas database was used to analyze the expression of HOXD13 and its effect on the survival rate of colon cancer patients. Wound healing, Transwell, and clone formation were used to evaluate the effects of changes in HOXD13 expression on the function of colon cancer cells. A nude mouse x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Transwell Invasion Assay. Transwell experiment was used to detect cell invasion ability as reported previously [52]. Briefly, matrixgel was spread onto the upper chamber.…”
Section: Cck8 Assaymentioning
confidence: 99%
“…Transwell Invasion Assay. Transwell experiment was used to detect cell invasion ability as reported previously [52]. Briefly, matrixgel was spread onto the upper chamber.…”
Section: Cck8 Assaymentioning
confidence: 99%
“…Among the top 100 DNA methylation sites in the BLCA network, multiple sites, such as cg24701780, cg24804145, cg15192120, and cg25497530, are all located on the PTPRN2 gene, and the average correlation between them was , which was larger than that averaged over the top 100 DNA methylation sites. This gene encodes a protein with sequence similarity to the receptor-like protein tyrosine phosphatase, which accelerates cancer progression and metastasis [ 72 , 73 ]. In Table S3 , we summarize the correlation coefficients for the sites on the same gene.…”
Section: Resultsmentioning
confidence: 99%
“…The 2q31.1 region is resided mainly by HOXD genes. Previous studies in other cancer types have suggested a potential oncogenic role for HOXD genes, but the underlying mechanism is not clear [21,22,40]. Inhibition of the transcription of the HOXD locus was suggested to be relevant with tumor-cell immune escape [41].…”
Section: Discussionmentioning
confidence: 99%